Shariah governance for Islamic financial institutions: lessons from Malaysia - Ahmed Sulub, Yasin; Haron, Razali (2289-1560, 2024)
Shariah governance (SG) refers to a framework designed to ensure that Islamic financial institutions (IFIs) adhere to Shariah principles in their operations and activities. This study examines SG practices in Malaysia, one of the top countries in Islamic finance governance, and discusses the lessons that can be drawn from them. The analysis focused on SG guidelines implemented in Malaysia, which provide a structured approach to ensuring Shariah compliance. The key lessons derived from these practices include the establishment of a comprehensive regulatory framework for Islamic finance governance, the implementation of dual SG structures, the enhancement of Shariah committee roles, the adoption of internal Shariah control functions, the promotion of accountable boards and management, and the incorporation of transparent approaches to SG practices. These insights offer valuable guidance for countries aiming to develop and strengthen their Islamic finance governance frameworks.